Structure of an Ancient Egyptian Tomb Inferred from Ground‐Penetrating Radar Imaging of Deflected Overburden Horizons. Issue 1 (22nd October 2014) - Booth, Adam D.; Szpakowska, Kasia; Pischikova, Elena; Griffin, Kenneth
Abstract Geophysical data acquisitions in most archaeological campaigns aim to image the target structure directly. The presence of a target, however, may be inferred from its interaction with surrounding layers, if its relationship with those layers can be characterized sufficiently. In this paper, we show the use of ground‐penetrating radar (GPR) to detect the subsurface continuation of the Ancient Egyptian tomb of the high‐official Karakhamun (Theban Tomb 223) at the South Asasif tomb complex (Luxor, Egypt). Data were acquired using a Sensors & Software pulseEKKO PRO system, equipped with antennas of 500 MHz centre‐frequency, on a silty–sandy sediment surface directly over the target structure. A test vertical radar profile (VRP) suggested that the tomb superstructure was buried too deeply beneath sedimentary overburden to be imaged directly: 500 MHz energy would propagate for only 2 m before becoming undetectable. Attenuative layers within that overburden were strongly reflective, however, and could be used to provide indirect evidence of any underlying structure. When observed in the GPR grid, these layers showed a discrete zone of deflection, 0.9 m in amplitude and 4 m wide, aligned with the long‐axis of the tomb. This deflection was attributed either to a collapsed vestibule beneath the survey site, or sediment settling within an unroofed staircase descending from ground‐ to tomb‐floor‐level; supporting evidence of this was obtained towards the end of the excavation campaign and in the following year. We highlight the value of such indirect imaging methods as a potential means of improving the capabilities of a given geophysical survey system, in this case allowing the GPR to characterize a target at greater depth than would typically be considered practical. © 2014 The Authors. Archaeological Prospection published by John Wiley & Sons Ltd.